A facile one-step hydrothermal approach to synthesize hierarchical core–shell NiFe2O4@NiFe2O4 nanosheet arrays on Ni foam with large specific capacitance for supercapacitors. Issue 27 (23rd April 2018) - Zhang, Xinyang; Zhang, Ziqing; Sun, Shuanggan; Wu, Yunpeng; Sun, Qiushi; Liu, Xiaoyang
Abstract : Hierarchical NiFe2 O4 @NiFe2 O4 core–shell nanosheet arrays synthesized via one-step hydrothermal method with a successive annealing exhibited outstanding electrochemical performance. Abstract : In this contribution, NiFe2 O4 @NiFe2 O4 nanosheet arrays (NSAs) with three-dimensional (3D) hierarchical core–shell structures were synthesized by a facile one-step hydrothermal method and they were used as electrode materials for supercapacitors (SCs). The NiFe2 O4 @NiFe2 O4 composite electrode showed a high specific capacitance of 1452.6 F g −1 (5 mA cm −2 ). It also exhibited a superior cycling stability (93% retention after 3000 cycles). Moreover, an asymmetric supercapacitor (ASC) was constructed utilizing NiFe2 O4 @NiFe2 O4 NSAs and activated carbon (AC) as the positive and negative electrode, respectively. The optimized ASC shows extraordinary performances with a high energy density of 33.6 W h kg −1 at a power density of 367.3 W kg −1 and an excellent cycling stability of 95.3% capacitance retention over 3000 cycles. Therefore, NiFe2 O4 @NiFe2 O4 NSAs have excellent pseudocapacitance properties and are good electrode materials for high energy density.